2022
DOI: 10.1021/acs.est.1c04704
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Photochemical Transformation of Hg Species and Associated Isotopic Fractionation in the Water Column of High-Altitude Lakes from the Bolivian Altiplano

Abstract: Photochemical reactions are major pathways for the removal of Hg species from aquatic ecosystems, lowering the concentration of monomethylmercury (MMHg) and its bioaccumulation in foodwebs. Here, we investigated the rates and environmental drivers of MMHg photodegradation and inorganic Hg (IHg) photoreduction in waters of two high-altitude lakes from the Bolivian Altiplano representing meso- to eutrophic conditions. We incubated three contrasting waters in situ at two depths after adding Hg-enriched isotopic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…27,35 These latter studies have overall evidenced a decrease of the photodegradation extents with increasing DOC concentrations, but the tipping point between enhancement and inhibition remains overall poorly defined. However, it has been suggested that 6−7 mg L −1 of DOC seem to be optimal conditions for MMHg photodegradation in natural waters, 23,34 and here we found it to be at its highest where the more terrestrial and highest concentrations of DOC are found in the Baltic Sea (i.e., averages of 16−18 μg L −1 for humic substances and 3.9 mg L −1 for DOC at Holmoarna and Harufjarden). It gives a new perspective to the negative relationship previously observed between MMHg and humic OM in the northern Baltic Sea, which was hypothesized to be caused by a reduced availability of Hg(II) for microbial MMHg formation.…”
Section: Odd Hg-mif In Seston Reflects In Situ Photochemical Reaction...supporting
confidence: 50%
See 2 more Smart Citations
“…27,35 These latter studies have overall evidenced a decrease of the photodegradation extents with increasing DOC concentrations, but the tipping point between enhancement and inhibition remains overall poorly defined. However, it has been suggested that 6−7 mg L −1 of DOC seem to be optimal conditions for MMHg photodegradation in natural waters, 23,34 and here we found it to be at its highest where the more terrestrial and highest concentrations of DOC are found in the Baltic Sea (i.e., averages of 16−18 μg L −1 for humic substances and 3.9 mg L −1 for DOC at Holmoarna and Harufjarden). It gives a new perspective to the negative relationship previously observed between MMHg and humic OM in the northern Baltic Sea, which was hypothesized to be caused by a reduced availability of Hg(II) for microbial MMHg formation.…”
Section: Odd Hg-mif In Seston Reflects In Situ Photochemical Reaction...supporting
confidence: 50%
“…Odd Hg-MIF is found in all fish samples, whatever the fish species or subbasins, with Δ 199 Hg ranging from 0.33 to 3.04‰ and Δ 201 Hg from 0.21 to 2.26‰ (Figure and Table SI-3). The Δ 199 Hg/Δ 201 Hg slope is 1.31 ± 0.02 (Figure c, linear fit, no weighting, p -value <0.005, n = 51) when considering all fish samples, which is typical for freshwater fish as it reflects the slope imprinted during MMHg photodegradation in freshwater with excess DOM compared to MMHg. ,,,,,, However, cod from Fladen present a lower Δ 199 Hg/Δ 201 Hg ratio of 1.08 ± 0.22 ( n = 5) compared to the other fish even if their MMHg content is similar (90.9–98.6%). This likely results from both their more pronounced benthic feeding that leads to the accumulation of both pelagic and benthic MMHg that is less or not photodegraded and their migration strategy.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, low DOM concentration promoted, whereas very high DOM concentration inhibited MeHg photodemethylation by DOM (Klapstein and O'Driscoll 2018). However, using Hg compound-specific stable isotope analysis it was shown in situ that MeHg photodegradation in natural waters mostly occurred in waters exposed to UV radiation and was modulated by the DOM level (Bouchet et al 2022). The photodemethylation of MeHg to iHg was shown to increase in the presence of fulvic acids while this process was limited in the presence of humic acids (Luo et al 2020).…”
Section: Abiotic Transformation Pathways Of Mercury Triggered or Infl...mentioning
confidence: 99%
“…The development of the Hg stable isotope fractionation approach opens up the possibility to decipher the contribution of interconnected abiotic and biotic transformation (Kritee et al 2013) and to track further the processes controlling origin and cycling of Hg before its incorporation in the foodweb (Bouchet et al 2022). Since the biotic transformations are considered prevailing, the development of the novel -omics approaches would provide key information on the interactions between Hg and phytoplankton species (Beauvais-Flück et al 2016, Beauvais-Flück et al 2018, Mangal et al 2022.…”
Section: Importantmentioning
confidence: 99%